Sociosexuality Is Associated With Disease Avoidance Tendencies and Can Decrease During a Real-Life Disease Threat - Sevi, Baris; Shook, Natalie J. (Springer, 2024)
Engaging in uncommitted sexual relationships increases the risk of pathogen transmission through close contact with novel partners. As such, greater disease avoidance tendencies may be associated with lower sociosexuality. Across three studies, we examined this proposition. In Studies 1a and 1b, we cross-sectionally assessed the associations between individual differences in disease avoidance (i.e., germ aversion, perceived infectability) and sociosexuality dimensions (i.e., behavior, attitude, desire). Greater germ aversion was significantly associated with more restricted sociosexuality across all three dimensions and replicated in both samples. Perceived infectibility was associated with more unrestricted sociosexual attitude and desire, but only in Study 1a. In Study 2, we tested whether sociosexuality levels changed with the COVID-19 pandemic. Participants reported more restricted sociosexuality levels during the COVID-19 pandemic compared to pre-pandemic levels, where a decrease was especially seen in sociosexual desire. Further, this decrease in sociosexual desire was predicted by pre-pandemic germ aversion levels. Overall, the findings indicate that disease avoidance tendencies (i.e., germ aversion) and real-life disease threat are associated with lower tendency to engage in uncommitted sexual relationships. Further research is needed to understand the causal relation of these two constructs, which may help in developing interventions and campaigns to support better sexual health.
Sevi, Baris/0000-0001-9663-4339
Keywords: Disease Avoidance; Sociosexuality; Behavioral Immune System; Germ Aversion; Individual Differences; Covid-19